HLA‐G 5′ URR SNPs and 3′ UTR 14‐bp insertion/deletion polymorphism in an Afro‐Brazilian population from Paraná State. (7th July 2013) - Tureck, L. V.; Santos, L. C.; Wowk, P. F.; Mattar, S. B.; Silva, J. S.; Magalhães, J. C. M.; Roxo, V. M. M. S.; Bicalho, M. G.
Summary The present study investigated 23 SNPs in the 5′URR promoter region and the 14 bp ins/del polymorphism at the 3′UTR region of the HLA‐G gene in 150 individuals with Afro‐Brazilian ancestry. Three haplotypes were found to be the most frequent. Comparing these polymorphisms in other samples, our data suggest that Afro‐Brazilians are more similar to the Euro‐Brazilians than to Hutterite population.